2014
DOI: 10.3922/j.psns.2014.042
|View full text |Cite
|
Sign up to set email alerts
|

Looming motion and visual attention.

Abstract: Motion perception is essential to adapt behavior in a dynamic environment. Many studies have suggested that looming motion captures attention, whereas receding motion does not, highlighting the behavioral urgency of motion perception. The present study examined whether attentional resources can be attracted by a specific directed flow in the presence of multiple flows that are simultaneously displayed in the visual field. The results showed that when two flows of opposite direction (looming and receding) are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
15
2
1
Order By: Relevance
“…Several studies in human adults highlighted the importance of perceiving and discriminating approaching trajectories (Abrams & Christ, , ; Cappe, Thut, Romei, & Murray, ; Franconeri & Simons, , ; Ghazanfar, Neuhoff, & Logothetis, ; Neuhoff, , ; Rosenblum, Carello, & Pastore, ; Rosenblum, Wuestefeld, & Saldaña, ; Rossini, ; Seifritz et al., ). These studies used either visual or auditory signals (or a combination of the same) and showed that looming stimuli—which specify impending collision (Howard & Rogers, )—receive a privileged processing.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies in human adults highlighted the importance of perceiving and discriminating approaching trajectories (Abrams & Christ, , ; Cappe, Thut, Romei, & Murray, ; Franconeri & Simons, , ; Ghazanfar, Neuhoff, & Logothetis, ; Neuhoff, , ; Rosenblum, Carello, & Pastore, ; Rosenblum, Wuestefeld, & Saldaña, ; Rossini, ; Seifritz et al., ). These studies used either visual or auditory signals (or a combination of the same) and showed that looming stimuli—which specify impending collision (Howard & Rogers, )—receive a privileged processing.…”
mentioning
confidence: 99%
“…For example, research using auditory looming showed that adults systematically underestimate the arrival time of a sound characterized by rising intensity (Rosenblum et al., ), that they perceive rising (i.e., approaching) sounds as closer to themselves compared to falling (i.e., receding) sounds (Rosenblum et al., ), and that they overestimate the change in intensity level of rising vs. falling sounds (Neuhoff, , ). Research that focused on the visual modality also provided evidence of the evolutionary importance of looming stimuli, demonstrating that looming motion can capture attention to a higher extent than receding motion (Abrams & Christ, , ; Franconeri & Simons, , ) and that the processing of looming stimuli is prioritized by the visual system (Rossini, ).…”
mentioning
confidence: 99%
See 3 more Smart Citations